2015
DOI: 10.1167/iovs.14-16021
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Retinal Photoreceptor Development in Very Preterm Compared to Term Infants

Abstract: Photoreceptor inner and outer segment development in VPT infants appears delayed when compared to term infants, and the photoreceptor RPE junction remains immature in all infants at TEA. Delayed maturation of photoreceptors could contribute to differences in visual function in some VPT infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 37 publications
6
61
2
Order By: Relevance
“…There are several differences in the results presented and those from OCT based human foveal development studies in infants (Dubis et al, 2012; Lee et al, 2015; Maldonado et al, 2011; Vajzovic et al, 2012; Vajzovic et al, 2015; Vinekar et al, 2015). Specifically, in preterm and term human infants, the foveal pit region has OCT bands indicating inner retinal components, whereas in the rhesus monkey, no evidence of ganglion cell layer or inner nuclear layer was seen on OCT imaging.…”
Section: 0 Discussionmentioning
confidence: 78%
“…There are several differences in the results presented and those from OCT based human foveal development studies in infants (Dubis et al, 2012; Lee et al, 2015; Maldonado et al, 2011; Vajzovic et al, 2012; Vajzovic et al, 2015; Vinekar et al, 2015). Specifically, in preterm and term human infants, the foveal pit region has OCT bands indicating inner retinal components, whereas in the rhesus monkey, no evidence of ganglion cell layer or inner nuclear layer was seen on OCT imaging.…”
Section: 0 Discussionmentioning
confidence: 78%
“…Maximum LIS depends on the location of the retina that is tested. Since we used bright mesopic conditions and a Goldmann I stimulus at 0° eccentricity, the detected LIS represents the cone visual system, similar to VA. An indication of the reason of the reduced LIS compared with term-born infants could be differences in morphology on SD-OCT suggestive of photoreceptor immaturity in premature infants 34. Correlation of LIS and VA has been performed with varying degrees of success in a number of pathologies, including diabetic macular oedema, idiopathic epimacular membrane or idiopathic macular telangiectasia 37 43–45.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of early retinal morphological data in premature infants with and without ROP seen with spectral domain optical coherence tomography (SD-OCT), this kind of information becomes increasingly interesting 34 35. Fundus-controlled perimetry provides a measurement of the light increment sensitivity (LIS) at defined loci within a 25° visual field and has allowed to detect small deficits in visual function in the parafoveal and macular area in other patient cohorts 36 37…”
Section: Introductionmentioning
confidence: 99%
“…Further studies with spectral domain OCT (SD-OCT) has shown that the inner retinal cells have not completed their peripheral migration and that seems to be associated with the increased thickness [17, 18]. A recent study by Vajzovic et al [19] using hand-held OCT showed a delayed photoreceptor development in preterm children compared to children born at term when investigated at 37 weeks of gestation and onward. It is not known whether this delay in maturation affects the photoreceptors later in life.…”
Section: Discussionmentioning
confidence: 99%